Scientometric Portrait of Nobel Laureate Harold W.Kroto - Kademani, B. S.; Kalyane, V. L.; Kumar, Vijai (Journal of Information and Knowledge, 2002)
Scientometric analysis of 190 publications by Harold W. Kroto, the Nobel laureate in Chemistry (1996) published during 1985 - 2000 in domains: Fullerenes (109), Cluster Science (39) , Spectroscopy of Unstable Species and Reaction Intermediates (8), Astrophysics (16), and Non Carbon Nanostructures (18) were analysed for authorship pattemwith his 181 collaborators. Highest collaborations were with D. R. M. Walton (142), R. Taylor (90), J. P. Hare (60) , K. Hsu (53), M. Terrones (48), A.D. Darwish (36), P.R. Birkette (35) and H. Terrone (35). His productivity coefficient was 0.68 which clearly indicates that his productivity increased after 50 percentile age of his 16 years of research publication career. His highest collaboration coefficient (1.00) was found in 1985,1993,1995,1996,1998 - 2000. Publication concentration was 4.5 and publication density was 3.05. Average Bradford multiplier was 3.5. The core journals publishing his papers were: J. Chern. Soc. Chern. Commun.(23). Chern. Phys. Lett. (20), J. Chem .Soc. Perkin Trans.-2 (15). and Nature (10) out of 59 journal and 13 other channels. Most prolific keywords in titles were: C60IFullerenes/[60] Fullerene/Buckrninsterfullerene, C70/[70] Fullerenes. Fonnation, and Characterisation.